The incidence of fungal infections in pancreas transplant recipients in the absence of systemic antifungal prophylaxis. Issue 10 (30th August 2019) - Shaikh, Suhail A.; Zimmerman, Asha; Nolan, Annelise; Cooper, Matthew; Abrams, Peter L.
Abstract: Background: There is a lack of high‐level evidence identifying meaningful outcomes and the place in therapy for systemic perioperative antifungal prophylaxis (ppx) in pancreas transplant recipients. As our program does not routinely utilize systemic perioperative antifungal ppx in pancreas transplant recipients, we assessed the incidence of post‐transplant infectious complications. Methods: This was a single‐center, retrospective cohort study of consecutive adult pancreas transplant recipients between 01/2016 and 04/2018 to describe the incidence of fungal infections. Patients with a history of previous simultaneous pancreas‐kidney (SPK) transplant, HIV, or unexplained use of antifungal ppx after transplantation were excluded. The primary outcome was the incidence of fungal infections within 3 months after transplantation. Results: After screening 60 patients, 56 met inclusion criteria. Within 3 months post‐transplantation, two (3.6%) patients had a positive fungal culture requiring systemic antifungal treatment. The sources for infection in both cases were intra‐abdominal fluid cultures, positive for Candida albicans . Both patients were treated with fluconazole. Allograft‐related outcomes included a 6‐month pancreas graft survival of 91.1% and pancreas transplant rejection incidence of 10.7%. Conclusion: In this single‐center experience, pancreas transplant recipients not receiving systemic antifungal ppx had similar infectious and graft‐related outcomes to what is reported in literature.